췌두부십이지장절제술 후 췌공장문합부 누출의 위험인자에 대한 연구 - 고호영(Ho Young Ko); 박동은(Dong Eun Park); 오정택(Jung Taek O); 권정남(Jung Nam Kwon); 소병준(Byung Jun So); 채권묵(Kwon Mook Chae) (Annals of surgical treatment and research, 2005)
Purpose: Pancretojejunostomy leakage is the most dreaded complication after a pancratoduodenectomy. However, little is known about what causes the leakage and how to prevent it. The aim of this study was to dentify the risk factors for pancreatic leakage. This paper describes our experience of its management. Methods: Between Aug. 1996 and Aug. 2003, 75 consecutive patients with periampullary cancer or benign disease received a pancreatoduodenectomy. The patients' clinical characterisitcs, pathological features and surgical findings were retrospectively evaluated. The patients were classified into those with major complication and rhose with no complications and the risk factors were analyzed. Pancreatic leakage, intraabdomnial fluid collection and abscess, intraabdomnial bleeding were categorized as major complications related to a pancreatic fistula. Results: The postoperative mortality and morbidity rate was 2.6% and 36%, respectively. Univariate analysis showed that the pancreatic texture, pathologic diagnoses and comorbidity were significant risk factors for major complications (P= 0.003, 0.045, 0.02). Multivariate analyses revealed that the, pancreatic texture was the only significant risk factor (P=0.003). The preoperative serum albumin level and pancreatic texture were significant risk factors for pancreatic leakage (p=0.03, 0.025) and multivariate analysis showed that the pancreatic texture was also the most significant risk factor. Conclusion: Considering that the pancreatic texture is the most significant risk factor for a pancreatic fistula, the technical skill and experience of the surgeon appears to be important for its prevention. KCI Citation Count: 1